Board characteristics and early adoption of MASB 22 (segment reporting) in Malaysia - Wan Hussin, Wan Nordin; Che Adam, Noriah; Lode, Nor Asma; Kamardin, Hasnah (2004)
This study examines whether there are systematic differences between early adopters and a matched control group of non-early adopters of Malaysian Accounting Standards Board 22 on segment reporting.Using a sample of 32 early adopters and a matched-pair of non-early adopters, our findings show that early adopters have significantly higher proportion of non-executive directors, particularly non- independent non-executives, than non-early adopters.Further analysis shows that fill early adopters are significantly larger in size than non-early adopters, but partial early adopters are significantly smaller in size than non-early adopters.Furthermore, partial adopters also tend to have significantly greater proportion of non-executive directors (especially non-independent) than non-early adopters.